Geophysical Site Characterization and monitoring of CO2 mineralization in Basaltic Complexes, Helguvik, Iceland - Junker, Jonas Simon; Obermann, Anne; id_orcid:0 000-0001-6933-6301; Zappone, Alba Simona; id_orcid:0 000-0003-0965-7271; Maurer, Hansruedi; Wiemer, Stefan; id_orcid:0 000-0002-4919-3283 (Copernicus, 2024)
In a pilot project (DemoUpStorage) in Helguvik, Iceland, CO2 is injected into basaltic strata using seawater instead of freshwater for CO2 dissolution. The aim is to obtain permanent storage of the CO2 by mineral carbonation. We aim to observe the precipitation of Mg and Fe carbonates in the porosity of the reservoir at depth. Additional to geochemical observations, we use geophysical methods (ERT, seismics) to monitor the mineralization process. Here, we present the overall project, the geophysical characterization of the site and the first time-lapse monitoring results. We performed a cross-hole seismic traveltime tomography and single-hole electrical resistivity (ERT) measurements to characterize the study site in the target depth of 150m to 400m and to record a geophysical baseline for the time-lapse measurements. The seismic and geoelectric data are in good agreement, highlighting multiple basaltic layers of tens of meters in thickness with sedimentary interlayers. With the CO2 injection starting in early 2024, we will also show the first results from the (daily) time-lapse ERT surveys.